COMPUTATION OF THE GAP SIZE AT THE MARGINAL INTERFACE OF TWO TYPES OF FISSURE SEALANTS: AN IN VITRO EXPERIMENTAL STUDY - Khan, Tabinda Nawaz; Khan, Farhan Raza; Riaz, Muhammad Fahad (Journal of Ayub Medical College Abbottabad, 2025)
Background: The occlusal surface, prone to dental caries due to pits and fissures formed by imperfect enamel coalescence, is commonly protected using fissure sealants. This study evaluated the gap size at the tooth-sealant interface for two sealant types, with and without enameloplasty. Methods: An in vitro experimental study was conducted at Dow Dental College, Karachi. Forty-four extracted human molars and premolars were divided into four subgroups based on sealant type—light-cured flowable resin-based or resin-modified glass ionomer cement (RMGIC)—and whether enameloplasty was performed. Specimens underwent thermocycling, sectioning, drying, and gold sputtering. They were examined at 50× magnification using scanning electron microscopy. Slides showing gaps between sealants and tooth structures were analyzed. One-way ANOVA tested the mean gap differences, with significance set at p≤0.05. Results: The overall mean gap observed was 22.38±14.33 µm. The largest gap (30.68±17.76 µm) appeared in RMGIC without enameloplasty; the smallest (12.12±7.03 µm) in flowable resin with enameloplasty. RMGIC with enameloplasty and flowable resin without enameloplasty showed comparable mean gap sizes (20.51±8.04 µm). Differences among groups were statistically significant (p=0.007). Conclusion: Flowable resin-based sealants created smaller marginal gaps than RMGIC. Enameloplasty significantly reduced gaps in both sealant types, with the most pronounced improvement observed in the flowable resin group.